Factors That Influence The Performance Of Emergency Installation Nurses At Bunda Thamrin Medan Hospital in 2018 - Hendry, Hendry (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2022)
Nurses as one of health workers in the hospital having an important role in achieving health development goals. The success of health services depends on the participation of nurses to provide high quality care nursing for patients . This research is quantitative and uses cross sectional design. The purpose of this research is to see what factors that can influence the performance of the emergency room in Bunda Thamrin Hospital Medan 2018. This research use total sampling or exhausted sampling and The source data of this research is using questionnaires and then followed by using univariate analysis, bivariate analysis, and multivariate analysis with the SPSS program. The results of this research is that work load (p=0,000), stress of work (p=0,000),competition (p=0,000), incentive (p=0,000),length of working (p=0,000) have influences for performance of nurses. After multivariate analysis the most influential variable is work load (p=0,000. The result showed that there was correlation between work load, stress of work, competition, incentive, length of working has influences against work performances of nurses. Therefore, there is a need to improve nursing service that can be made to improve the performance of nurses with increased knowledge through education nursing sustainable and improving skills nursing is absolutely necessary. The arrangement of a work conducive environment is so important, so that nurses can work effectively and efficiently .Creating a work that could lead to a nurse to do the best. Keywords : nurse performance, work load, work stress, competition, incentive, length of working